Sounds Like Home : Growing Up Black and Deaf in the South - Wright, Mary Herring, 1924-2018 (Book collections on Project MUSE., 1999)
Mary Herring Wright's story adds an important dimension to the current literature in that it is a story by and about an African American deaf child. Her story is unique and historically significant because it provides valuable descriptive information about the faculty and staff of the North Carolina school for Black deaf and blind students at that time from the perspective of a student as well as a student teacher. In addition, this engrossing narrative contains details about the curriculum, which included a week-long Black History celebration where students learned about important Blacks such as Madame Walker, Paul Laurence Dunbar, and George Washington Carver. It also describes the physical facilities as well as the changes in those facilities over the years. In addition, the story occurs over a period of time that covers two major events in American history, the Depression and World War II. Wright's account is one of enduring faith, perseverance, and optimism. Her keen observations will serve as a source of inspiration for others who are challenged in their own ways by life's obstacles.